Analysis of Financial Literacy for Business Sustainability with Entrepreneurial Characteristics as a Mediation Variable (Survey on Food Processing SMEs in Sukabumi City) - Pryal, Agitya Nur; Danial, R. Deni Muhammad; Jhoansyah, Dicky (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research examines financial literacy and entrepreneurial characteristics as factors that influence business sustainability in food processing SMEs in Sukabumi City. The results show that good financial literacy is positively related to maintaining business sustainability in these SMEs. However, although entrepreneurial characteristics mediate the relationship between financial literacy and business sustainability, the impact is not statistically significant. This shows that other factors influence this relationship in Sukabumi City food processing SMEs.